Alzheimer’s disease and language impairments: social intervention and medical treatment - Klimova, Blanka (Clin Interv Aging, 2015)
Communication is very important for people to be successfully integrated into social environment and make and maintain relationship. Particularly, language difficulties lead to social exclusion of the people affected with Alzheimer’s disease (AD) and contribute to a significant decrease in the quality of their life and also have a big impact on their family members who in most cases become their caregivers who need to communicate with their loved ones in order to meet their needs. Therefore, the goal of this study is to describe language impairments in the individual phases of AD and discuss their improvement with respect to AD on the basis of literature review. The authors of this article use traditional research methods in order to achieve the goal set mentioned earlier. First, a method of literature review of available sources describing language impairments in the individual phases of AD is exploited. Second, to show how informal caregivers and relevant drugs can successfully intervene in the improvement of these language impairments, a method of comparison of different research studies exploring such social intervention and medical treatment is used.